Smaller size is more suitable for pharmacotherapy among undersized abdominal aortic aneurysm: A systematic review and meta-analysis. (June 2022) - Shirasu, Takuro; Takagi, Hisato; Yasuhara, Jun; Kuno, Toshiki; Kent, K Craig; Clouse, W Darrin
Background: Pharmacotherapy for undersized abdominal aortic aneurysm (AAA) is a clinical unmet need. Randomized controlled trials (RCTs) have failed to show effectiveness despite countless promising data in preclinical studies. We aimed to identify the population with undersized AAAs (30–54 mm) who potentially benefit from pharmacotherapy.Methods: In accordance with the PRISMA statement, we conducted a systematic review and meta-analysis of placebo-controlled RCTs. The primary outcome was mean difference (MD) in annual growth rate (< 0 favors pharmacotherapy), and the secondary outcome was aneurysm-related events (diameters ⩾ 55 mm, ruptures, or referral to surgery).Results: Our search strategy identified eight RCTs (six trials on antibiotics [ABx], two on renin-angiotensin system inhibitors [RAS-I]) with a total of 1325 patients. The mean of baseline diameters ranged from 33.1 mm to 43.1 mm. Neither ABx nor RAS-I showed significant differences in MD. Multivariable random-effects restricted maximum likelihood meta-regression revealed a statistically significant linear relationship between baseline diameter and MD (coefficient 0.15 [95% CI 0.0011, 0.30], p = 0.049) but not for the follow-up period ( p = 0.28) and duration of treatment ( p = 0.11). In line with this result, ABx with baseline diameter < 40 mm significantly reduced MD (−1.03 mm/year [95% CI −1.64, −0.42], p = 0.001) and a borderline significant difference in aneurysm-related events (HR 0.53 [95% CI 0.28, 1.00], p = 0.05), whereas the other groups ⩾ 40 mm never demonstrated effectiveness. Fixed-effect models did not change the results. No evidence of publication bias was detected.Conclusion: Undersized AAAs < 40 mm can potentially benefit from pharmacotherapy. Future RCTs should consider preferentially including undersized AAA with smaller diameters.